2018
DOI: 10.1016/j.envint.2018.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Elevated concentrations of urinary triclocarban, phenol and paraben among pregnant women in Northern Puerto Rico: Predictors and trends

Abstract: Background: Understanding important sources and pathways of exposure to common chemicals known or suspected to impact human health is critical to eliminate or reduce the exposure. This is particularly important in areas such as Puerto Rico, where residents have higher exposures to numerous chemicals, as well as higher rates of many adverse health outcomes, compared to the mainland US. Objective: The aim of this study was to assess distributions, time trends, and predictors of urinary triclocarban, phenol, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 93 publications
8
48
1
2
Order By: Relevance
“…In addition, MPB and PPB were highly correlated (r = 0.84), likely re ecting similar usage in consumer products. In line with previous studies using repeated measures of these biomarkers, there was poor-to-fair stability for all analytes measured (0.25 ≤ ICC ≤ 0.74; Additional File 1: Supplemental Table 4) (10,11,48). Abbreviations: IQR = interquartile range; aOR = adjusted odds ratio 1 Models adjusted for age (years), pre-pregnancy BMI (kg/m 2 ), maternal race (white/Black/other), maternal education (high school or less/some college or technical school/completed college or greater), and fetal sex (female/male).…”
Section: Characteristics Of Urinary Exposure Biomarkerssupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, MPB and PPB were highly correlated (r = 0.84), likely re ecting similar usage in consumer products. In line with previous studies using repeated measures of these biomarkers, there was poor-to-fair stability for all analytes measured (0.25 ≤ ICC ≤ 0.74; Additional File 1: Supplemental Table 4) (10,11,48). Abbreviations: IQR = interquartile range; aOR = adjusted odds ratio 1 Models adjusted for age (years), pre-pregnancy BMI (kg/m 2 ), maternal race (white/Black/other), maternal education (high school or less/some college or technical school/completed college or greater), and fetal sex (female/male).…”
Section: Characteristics Of Urinary Exposure Biomarkerssupporting
confidence: 88%
“…First, we were able to assess prenatal exposure to consumer product chemicals using measurements from up to three study visits during pregnancy. As this study and others have demonstrated, the stability of consumer product chemical concentrations in urine is often low given their short half-lives (10,11,48). Yet, many studies continue to rely on a single spot urine sample to assess prenatal exposure to these chemicals (1), and therefore, may be more susceptible to bias due to exposure misclassi cation (73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomarkers of exposure for several contaminants have been found to be elevated among pregnant women in this cohort, including several phthalates (Cantonwine et al 2014), phenols (Meeker et al 2013), certain polycyclic aromatic hydrocarbons (Cathey et al 2018), and certain metals, compared to female participants in the National Health and Nutrition Examination Survey (NHANES) aged 18-40. Notably, we recently reported that the antibacterial compounds triclosan and triclocarban were significantly higher in PROTECT women compared to NHANES (Ashrap et al 2018). However, exposure to persistent organic pollutants (POPs), specifically polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs), per-and polyfluoroalkyl substances (PFASs), and polybrominated diphenyl ethers (PBDEs), has not previously been evaluated within the PROTECT cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these properties, PFASs have been used in numerous consumer products, including stain repellants, textiles, cookware, food packaging, cleaning products, and fire-fighting foams (UEPA (EPA) 2018). Exposure to longer chain PFASs, such as perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS), has been associated with increased risk of cancer, low birth weight, and immune and endocrine system disruption (Bach et al 2015;DeWitt et al 2018;Grandjean et al 2017;Rappazzo et al 2017;Steenland et al 2010). Although longer chain PFASs have been phased out of use in the US, use of shorter chain replacement PFASs has increased despite limited information on their toxicity (Birnbaum and Grandjean 2015;Brendel et al 2018).…”
Section: Introductionmentioning
confidence: 99%